Rapid analysis of Forster resonance energy transfer by two-color global fluorescence correlation spectroscopy: trypsin proteinase reaction. - Eggeling, C; Kask, P; Winkler, D; Jäger, S (2005)
In this study we introduce the combination of two-color global fluorescence correlation spectroscopy (2CG-FCS) and Förster resonance energy transfer (FRET) as a very powerful combination for monitoring biochemical reactions on the basis of single molecule events. 2CG-FCS, which is a new variation emerging from the family of fluorescence correlation spectroscopy, globally analyzes the simultaneously recorded auto- and cross-correlation data from two photon detectors monitoring the fluorescence emission of different colors. Overcoming the limitations inherent in mere auto- and cross-correlation analysis, 2CG-FCS is sensitive in resolving and quantifying fluorescent species that differ in their diffusion characteristics and/or their molecular brightness either in one or both detection channels. It is able to account for effects that have often been considered as sources of severe artifacts in two-color and FRET measurements, the most prominent artifacts comprising photobleaching, cross talk, or concentration variations in sample preparation. Because of its very high statistical accuracy, the combination of FRET and 2CG-FCS is suited for high-throughput applications such as drug screening. Employing beam scanning during data acquisition even further enhances this capability and allows measurement times of <2 s. The improved performance in monitoring a FRET sample was verified by following the protease cleavage reaction of a FRET-active peptide. The FRET-inactive subpopulation of uncleaved substrate could be correctly assigned, revealing a substantial portion of inactive or missing acceptor label. The results were compared to those obtained by two-dimensional fluorescence intensity distribution analysis.